Seasonal metabolic and growth responses of grazing beef heifers divergent in residual feed intake - Maria Camila Londono-Mendez; Sergio Lasso-Ramirez; Carolyn Fitzsimmons; Graham Plastow; Edward W. Bork; John Basarab; Ana Caroline Cerqueira de Melo Vasco; Aghata Elins Moreira Silva; Arturo Macias Franco; Michael Vinsky; Changxi Li; Gleise Medeiros da Silva (PLoS ONE, 2026)
This study involved 41 crossbred, black-hided beef heifers that were measured in a drylot for residual feed intake (RFI) at 11 ± 1 months of age and classified into more (LOW-RFI; n = 21; –0.96 ± 0.70 kg DM/day) or less efficient (HIGH-RFI; n = 20; 1.40 ± 1.00 kg DM/day) groups. Heifer metabolism and growth performance were evaluated from 14 ± 1 months of age (351 ± 40 kg initial body weight [BW]) across summer and winter in Western Canada. Weather conditions were characterized using the Comprehensive Climate Index (CCI). Rumen temperature (RT) was recorded every 10 minutes using an automated bolus device. Plasma and BW were collected every 18 ± 5 days from July to August and January to March to measure urea nitrogen, non-esterified fatty acids, insulin-like growth factor 1, β-hydroxybutyric acid, leptin, free triiodothyronine (fT 3 ), haptoglobin, heat shock protein 70 (HSP70), gamma-aminobutyric acid, and serotonin, and growth performance. Data were analyzed as a completely randomized design using SAS 9.4. LOW-RFI tended to have greater fT 3 and HSP70 ( P = 0.08), while exhibiting lower haptoglobin concentrations ( P = 0.02) in summer. Gamma-aminobutyric acid concentrations were greater in LOW-RFI during periods of no heat stress ( P = 0.01) and tended to decrease in HIGH-RFI under severe risk of cold stress ( P = 0.08) based on CCI. Comparatively, HIGH-RFI had higher leptin concentrations during winter ( P = 0.04) than LOW-RFI. During summer, HIGH-RFI exhibited greater RT between 1:00–6:00, 10:00–12:00, and 20:00–22:00 ( P = 0.002). In contrast, HIGH-RFI had lower RTs on the coldest winter days ( P = 0.009). In both seasons, growth performance did not differ between RFI groups ( P ≥ 0.24). In conclusion, feed efficiency measured in the drylot was associated with subsequent metabolic responses during grazing, and these responses were influenced by weather-related stress, with more efficient animals showing greater adaptability to weather fluctuations.